Age related changes in apoptosis of germ cells in normal and dibutyl phthalate-treated testes of Japanese quail (Coturnix coturnix japonica) - McGaw, Lyndy Joy (University of Pretoria, 2024)
Thesis (PhD)--University of Pretoria, 2021.